A Study on Some Properties of Polypropylene Based Nanocomposites Made Using Almond Shell Flour and Organoclay - Lashgari, Amir; Eshghi, Ayoub; Farsi, Mohammad (Asian Journal of Chemistry, 2012)
The effect of nanoclay (NC) loading (0, 2.5 and 5 phr) and almond shell flour (ASF) content (30, 35 and 40 %) on the strength properties of polypropylene composites was evaluated. The amount of maleic anhydride grafted polypropylene (PP-g-MA) was constant at 2 phr for all formulations. The composite compounds were formed using a counter-rotating twin screw extruder and the specimens were made in an injection molding machine. The mechanical properties such as tensile, flexural and impact strength were measured. Results revealed the fact that when nanoclay and almond shell flour were added, the flexural and tensile modulus increased significantly, but both flexural and tensile strengths decreased slightly. The impact strength was 8 % lower besides adding 2.5 phr nanoclay, but at 5 phr nanoclay, the property was reduced to 19.6 %. At higher incorporation of both almond shell flour and nanoclay, the impact strength of composites was decreased more. The morphology of the composites containing different levels of nanoclay and almond shell flour has been examined by using X-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. XRD findings showed that with increasing nanoclay content the peak was shifted to a lower angle, which implies formation of the intercalation morphology. The mechanical properties of the composites blends made with almond shell flour were further supported by SEM micrographs.